2016
DOI: 10.1111/1365-2435.12677
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhizal and saprotrophic fungal guilds compete for the same organic substrates but affect decomposition differently

Abstract: 1. Communities of litter saprotrophic and root-associated fungi are vertically separated within boreal forest soil profiles. It is unclear whether this depth partitioning is maintained exclusively by substrate-mediated niche partitioning (i.e. distinct fundamental niches), or by competition for space and resources (i.e. distinct realized niches). Improved understanding of the mechanisms driving spatial partitioning of these fungal guilds is critical, as they modulate carbon and nutrient cycling in different wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
148
2
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(162 citation statements)
references
References 59 publications
10
148
2
2
Order By: Relevance
“…In boreal forests which are known to be N limited, ECM and SAP fungi are spatially separated. SAP fungi tend to colonize more recently shed litter at the forest floor surface and mycorrhizal fungi are more abundant in the underlying layers which contain older, more decomposed litter (Lindahl et al 2007;Clemmensen et al 2013;Bödeker et al 2016). Whether this vertical separation is the result of competitive exclusion of saprotrophic fungi by ECM or niche differentiation needs to be addressed (Fernandez and Kennedy 2015).…”
Section: The N Inhibition Hypothesismentioning
confidence: 99%
See 2 more Smart Citations
“…In boreal forests which are known to be N limited, ECM and SAP fungi are spatially separated. SAP fungi tend to colonize more recently shed litter at the forest floor surface and mycorrhizal fungi are more abundant in the underlying layers which contain older, more decomposed litter (Lindahl et al 2007;Clemmensen et al 2013;Bödeker et al 2016). Whether this vertical separation is the result of competitive exclusion of saprotrophic fungi by ECM or niche differentiation needs to be addressed (Fernandez and Kennedy 2015).…”
Section: The N Inhibition Hypothesismentioning
confidence: 99%
“…Whether this vertical separation is the result of competitive exclusion of saprotrophic fungi by ECM or niche differentiation needs to be addressed (Fernandez and Kennedy 2015). Bödeker et al 2016 tried to address this question by investigating the vertical positions of saprotrophic and ECM fungi in the soil profile and the potential for different fungal guilds to colonize substrates of varying quality. The results from their study support the idea that SAP and ECM fungi have overlapping fundamental niches, in that both were able to colonize the same substrates and their vertical separation in the soil is likely reinforced by competition for N (Bödeker et al 2016).…”
Section: The N Inhibition Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…However, studies have also demonstrated that some EM fungi may have similar oxidative and hydrolytic enzymatic capacities to saprotrophic fungi (Bödeker, Nygren, Taylor, Olson, & Lindahl, 2009;Firoz, 2014;Phillips, Ward, & Jones, 2014), and that gene expression for their oxidative degradation may be regulated by belowground tree C allocation (Rineau et al, 2013;Voříšková, Brabcová, Cajthaml, & Baldrian, 2014). Furthermore, a recent study conducted in a boreal forest suggested that saprotrophic and EM fungi may have overlapping niches with regard to their colonization of different substrate qualities, suggesting that EM fungi may colonize fresh litter as well as humus (Bödeker, Lindahl, Olson, & Clemmensen, 2016). While it is clear that both EM fungi and saprotrophic microbiota (i.e., fungi and other microbes) play an important role in decomposition, less is known about how N enrichment influences the relative contribution of these functional groups to the decomposition of new (fresh litter) versus old substrates (humus).…”
Section: Introductionmentioning
confidence: 99%
“…High throughput sequencing has revolutionized microbial ecology. We now have the ability to characterize both prokaryotic and eukaryotic microbial communities more thoroughly and disentangle relationships among broad organismal groups (Bödeker et al ., ; Morriën et al ., ; Toju et al ., ). Arbuscular mycorrhizal fungi (AMF; subphylum Glomeromycotina, Spatafora et al ., ) are no exception, and high throughput sequencing has revealed greater richness within communities compared with Sanger sequencing (Öpik et al ., ), as well as an increased understanding about global distribution patterns and their potential underlying drivers (Davison et al ., ).…”
Section: Introductionmentioning
confidence: 99%